Pengaruh Kompetensi Sumber Daya Manusia, Budaya Organisasi, Dan Pemanfaatan Teknologi Informasi Terhadap Pengelolaan Alokasi Dana Desa Di Kabupaten Jembrana - Purbasari, Putu Intandika; Yuniarta, Gede Adi (Jurnal Akuntansi Profesi, 2020)
This study aimed at empirically proving the effect human resource competencies, organizational culture and utilization of information technology to manage village fund allocation in Jembrana district. This research was a quantitative study using primary data obtained from questionnaires and measured by using a Likert scale. The population in this study is the Village Government in Jembrana Regency. The sample in this study was determined based on the results obtained from calculations using the Slovin formula, because in sampling, the numbers must be representative so that research results can be generalized. Data analysis technique used is multiple linear regression analysis using IMB SPSS ver.20.0. The results of this research indicate that Human resource competence, Organizational culture, and Utilization of information technology had a positive influence on the management of village fund allocations.